Response of Soybean Genotypes Challenged by a Stink Bug Complex (Hemiptera: Pentatomidae) - Souza, E. S. [UNESP]; Silva, J. P. G. F. [UNESP]; Baldin, E. L. L. [UNESP]; Pierozzi, C. G. [UNESP]; Cunha, L. S.; Canassa, V. F. [UNESP]; Pannuti, L. E. R. [UNESP]; Lourencao, A. L. (Oxford Univ Press Inc, 2016)
Pentatomids (stink bugs) are major pests of soybean, Glycine max (L.) Merril. These pests reach high levels of infestation, cause severe damage to seeds by feeding, are linked to leaf retention, and are difficult to control. Host plant resistance is considered to be a valuable tool in integrated pest management and can assist in reducing the damage caused by stink bugs. This research evaluated the resistance of soybean genotypes in Brazil to the stink bug complex, the Neotropical brown stink bug, Euschistus heros (F.), redbanded stink bug, Piezodorus guildinii (Westwood), southern green stink bug, Nezara viridula (L.), green belly stink bug, Dichelops melacanthus (Dallas), and Edessa meditabunda (F.), by assessing infestation assay, yield reduction, seed damage, and leaf retention. Certain genotypes expressed different categories of resistance: least infested, low yield reduction, low levels of damage in seeds, and low levels of leaf retention. PI lines and IAC 78-2318 showed antixenotic resistance, and 'IAC 100' showed tolerance for the stink bug complex. This is the first study to evaluate several parameters of yield and seed quality using different soybean maturity groups under relatively high infestation by the three stink bugs species. The promising genotypes might be used in regions with a high incidence of stink bugs to manage their populations in combination with other integrated pest management practices.
Keywords: host plant resistance; tolerance; antixenosis